Procedures For Preparation Of Financial Statements UMKM In Aqila Fishing Pool - Rasmon; Piliang , Arfa; Ulya , Syarifah; Tamba , Putriani; Helmida, Helmida (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2022)
Kulim District, Pekanbaru City, Riau has a fairly good environment in carrying out UMKM-scale business activities, especially in the fields of livestock, plantations and so on. UMKM start their business well, but there are weaknesses in the recording and preparation of inadequate financial reports. Based on the results of observations, it is known that one of the factors behind not carrying out accounting records is the inability of their human resources and a linear lack of knowledge to prepare financial reports for these UMKM. Thus, in order to help UMKM actors to carry out bookkeeping in a simple manner and according to applicable rules, community service for UMKM actors is carried out in preparing simple financial reports. The purpose of this PKM is for UMKM actors to apply simple accounting to their business activities. The method used is in the form of education and mentoring in the preparation of financial reports for UMKM actors in Aqila fishing ponds. Based on the evaluation of the results of this service, the management of the Aqila fishing pond understands and applies simple bookkeeping to their business.